2005
DOI: 10.5194/aab-48-445-2005
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive and milk performance merit of Butana cattle in Sudan

Abstract: Data from the Butana herd of Atbara Livestock Research Station were analyzed for the period 1949 -1999. The least squares means for age at first calving, calving interval, milk yield per lactation, daily milk yield, lactation length and dry period were 45.05 ± 3.56 months, 382.38 ± 8.30 days, 1662.57 ± 108.96 kg, 6.10 ± 0.40 kg, 268.17 ± 5.56 days and 119.10 ± 8.30 days, respectively. The analysis of variance revealed that the sire and parity number influenced the studied traits, while year-season of calving i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…However, Musa et al (2005) reported 112 days for Sudanese cattle, while Ishag (2000) found that the dry period for crossbred dairy cattle was 90.5 days. It is commonly estimated that a twomonth dry period provides a complete regeneration of udder glandular tissue and is favorable for the high production in the forthcoming lactation (Annen et al, 2004;Andersen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, Musa et al (2005) reported 112 days for Sudanese cattle, while Ishag (2000) found that the dry period for crossbred dairy cattle was 90.5 days. It is commonly estimated that a twomonth dry period provides a complete regeneration of udder glandular tissue and is favorable for the high production in the forthcoming lactation (Annen et al, 2004;Andersen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Other well-known beef-dairy cattle are Ogaden cattle (Small East African Zebu) ( Rege and Tawah, 1999 ), Jiddu cattle (Zenga) (Box, 1968), and Fogera cattle (Zenga) ( Gebremedhin et al, 2007 ). While the Kenana and Butana cattle from Sudan are amongst the best milk producing zebu breeds ( Musa et al, 2005 ).…”
Section: Characteristics Of African Indigenous Cattlementioning
confidence: 99%
“…Cattle are the main source of milk and meat in the Sudan and despite the huge numbers of cattle in the country (36 million heads according to AOAD, 2004) the Sudan has to import an appreciable proportion of its milk requirements. Although highly adapted to the local environment and to the needs of stockholders the indigenous types of cattle are mostly poor milk producers, but there are some promising local types (SAEED et al, 1987;MUSA et al, 2005). The need for a quick solution to the problem of the deficit in milk production has led to the importation of high producing European dairy breeds.…”
Section: Introductionmentioning
confidence: 99%